1997
DOI: 10.1111/j.0020-2754.1997.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Qualitative Research in Social Geography: Establishing ‘Rigour’ in Interview Analysis

Abstract: A review of 31 empirical and eighteen substantive papers by qualitative social geographers mainly using in-depth interviews reveals little explicit reference to the principle(s) adopted to enhance 'rigour' and to ensure meaningful inference. Given the modest explicit discussion of evaluative criteria in these papers, a scheme from evaluation research itself is critically reviewed. A set of evaluation questions derived from this review and their application to an empirical piece of qualitative work frame an arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
580
1
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(609 citation statements)
references
References 59 publications
4
580
1
12
Order By: Relevance
“…27,28 For the purposes of this review the following criteria were employed to gauge the quality of the studies identified in the search process. These criteria were based upon the work of scholars from the qualitative tradition 19,27,29,30 and to the Critical Appraisal Skills Programme 20 (see also Hammell 24 The most important aspect of quality for papers to be included in a meta-synthesis is clear evidence that the themes reported by the original researchers were rooted in the data; 17,20,26,27 thus papers were only included if there were adequate participants' perspectives to demonstrate the plausibility of the researchers' interpretations.…”
Section: Methodsmentioning
confidence: 99%
“…27,28 For the purposes of this review the following criteria were employed to gauge the quality of the studies identified in the search process. These criteria were based upon the work of scholars from the qualitative tradition 19,27,29,30 and to the Critical Appraisal Skills Programme 20 (see also Hammell 24 The most important aspect of quality for papers to be included in a meta-synthesis is clear evidence that the themes reported by the original researchers were rooted in the data; 17,20,26,27 thus papers were only included if there were adequate participants' perspectives to demonstrate the plausibility of the researchers' interpretations.…”
Section: Methodsmentioning
confidence: 99%
“…30 A number of guidelines exist for evaluating qualitative research. 21,26,36,43,44 However, the procedure for critiquing qualitative research is not one of judging rigid adherence to rules or specific prescriptive criteria, 45,46 but is a process of weighing the various elements of the research in an effort to determine their appropriateness given the purpose and context of the study. 44 Sandelowski et al 25 recommend using very general criteria for quality in evaluating the studies relevant to the systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…For the purposes of this review the following criteria were employed to gauge the quality of the studies, and were the guidelines for rigour that underpinned the present study. These criteria were formulated with reference to the work of scholars from the qualitative tradition 21,26,36,43 …”
mentioning
confidence: 99%
“…As this was a remotely conducted post-hoc project evaluation, information received in key informant interviews could not be cross-verified through a process of informant triangulation (Baxter and Eyles, 1997) in order to eliminate potential interviewee biases (Kumar, 1986). Ideally, with greater resources and time available, this study should have involved speaking with project participants, community members and other project staff in order to verify that key informants accurately described the project design and implementation, and did not over-or understate the level of project effectiveness or community involvement.…”
Section: Limitationsmentioning
confidence: 99%